Pengembangan Bahan Ajar Pendidikan Agama Katolik untuk Perguruan Tinggi Katolik Berbasis Pendekatan Deep Learning - Sergius Lay (Journal New Light, 2025)
This article discusses the development of teaching materials for Catholic Religious Education (CRE) at Catholic Higher Education Institutions (CHEIs) based on a deep learning approach. This study employs a qualitative literature review method to analyze relevant sources concerning the development of CRE teaching materials and the application of deep learning in religious education. The main findings suggest that deep learning can enrich the religious learning experience by emphasizing deep understanding, critical reflection, and the integration of Christian values in students' lives. The proposed model for developing teaching materials based on deep learning combines personalized learning, spiritual reflection, and the use of advanced technology. Despite challenges such as limited technological infrastructure and resistance to change, the study recommends strengthening technological infrastructure, providing faculty training, and implementing project-based learning methods. This study is expected to contribute to the development of more holistic and relevant Catholic religious education in CHEIs.